The Effectiveness of ethanol extract of Zingiber officinale var. rubrum on the expression of TNF-α, IRS and follicles in preventing polycystic ovary syndrome (PCOS) in reproductive health - Siti Mudrikatin; Lilis Suryani; Sukati Sarmin (Media of Health Research, 2026)
Polycystic ovary syndrome (PCOS) involves impaired ovulation and hyperandrogenism, elevating insulin and TNF-α levels, and disrupting insulin receptor substrate (IRS) formation. Zingiber officinale var. rubrum has been shown to suppress TNF-α, thereby enhancing IRS function and follicular development. This study evaluated whether red ginger extract attenuates TNF-α, upregulates IRS, and improves follicular development as a PCOS prevention strategy. Using a randomised post-test-only control group design, thirty Rattus norvegicus were divided into five groups (K−, K+, P1, P2, P3) and administered ethanol extract at 200, 400, or 800 mg/kg BW alongside testosterone propionate (100 mg/kg BW, i.p.) for 21 days. Tissues were assessed via HE staining and immunohistochemistry; LC-MS characterised extract composition. Ethical approval was obtained (No. 2.KEH.59.04.2025, Faculty of Medicine, Airlangga University). Red ginger extract significantly reduced TNF-α, increased IRS expression, and promoted follicular development. One-way ANOVA showed significant differences across all parameters (p = 0.001), with P1, P2, and P3 each differing significantly from the positive control.